2011
DOI: 10.1007/s00432-011-1049-2
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt and MAPK/ERK1/2 signaling pathways are involved in IGF-1-induced VEGF-C upregulation in breast cancer

Abstract: This study identified that PI3K/Akt and MAPK/ERK1/2 signaling pathways were involved in IGF-1-induced VEGF-C up-regulation and suggested their important roles in lymphatic metastasis in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 18 publications
7
77
1
1
Order By: Relevance
“…Increasing amounts of evidence have shown that hypoxia-induced abnormal proliferation of PASMCs is one of the major causes for hypoxic pulmonary arterial remodeling [11,41]. The ERK1/2 and PI3K/Akt signaling pathways have been recognized to mediate a wide range of functions, including proliferation, growth, and survival [42][43][44]. Besides, it has been demonstrated that they were crucial in mediating vascular smooth muscle cell proliferation in response to hypoxia exposure [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing amounts of evidence have shown that hypoxia-induced abnormal proliferation of PASMCs is one of the major causes for hypoxic pulmonary arterial remodeling [11,41]. The ERK1/2 and PI3K/Akt signaling pathways have been recognized to mediate a wide range of functions, including proliferation, growth, and survival [42][43][44]. Besides, it has been demonstrated that they were crucial in mediating vascular smooth muscle cell proliferation in response to hypoxia exposure [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated, silencing AURKA resulted in a decrease in mRNA levels of VEGF, providing an explanation for the inhibition of angiogenesis seen in the Matrigel assay. Several modes of VEGF transcriptional regulation have been cited in the literature including AKT-mediated induction in breast (22) and bladder (23) cancers. Interestingly, in our study, in addition to the effects seen on in vitro angiogenesis, silencing AURKA also resulted in decreased expression of pAKT (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Besides playing a crucial role in regulating cell growth, proliferation and differentiation, IGF-1R and its downstream signalling pathways have been implicated in the development of resistance to endocrine and targeted therapies (Gao et al , 2012; Karamouzis and Papavassiliou, 2012). In addition, a role in tumour cell migration and metastatic potential and a direct involvement in the metastatic cascade in breast have recently been proposed (Zhu et al , 2011). Interestingly, IGF-dependent enhanced cellular proliferation has been documented in TNBCs, which can provide new targets for the so far limited therapeutic options of this sub-type that lacks expression of other druggable targets, such as ER or HER-2 (Davison et al , 2011).…”
Section: Discussionmentioning
confidence: 99%